Pro-environmental or pro-social : Which motivation is stronger in the case of charity retailing engagement? - Borusiak, Barbara; Kucharska, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The aim of the study is to examine the intention to engage in charity retailing using the norm activation model which has been widely used to predict people’s altruistic and pro-social behavior (De Groot and Steg, 2009, 425–449). Pro-social behavior refers to a person’s action that is intended to help other people and consists of a broad range of helping, sharing, and cooperating behaviors. Three forms of engagement in charity retailing were taken into account: buying at a charity shop, volunteering in a charity store, and donating. The current study was conducted in 2019 using the CAWI method on 766 Polish students coming from 16 universities; for data analysis, SEM was applied. We tested two variants of the model. In the first one we connected personal norm, awareness of consequences, and ascription of responsibility with the context of the natural environment protection, whereas in the second the same variables were connected with helping people in general. The findings show that the norm activation model may be applied as a mediator model for explaining intention to engage in shop charity. Both tested models were positively verified — all relations but one were proven to be statistically significant. The only relation which turned out to be statistically insignificant was the relation between awareness of consequences and personal norm. The results show that environmental context increased the strength of the relations between the analyzed variables.
Keywords: charity retailing; pro-environmental motivation; pro-social motivation; norm activation model